Differences between passport and biological (actual) age in the population of Russian patients suffering from arterial hypertension (analysis of the «Hyperion» register) - A G Arutyunov; A V Nozdrin; K B Shavgulidze; D S Tokmin; I V Osadchiy (Терапевтический архив, 2018)
The age of the patient is the most important factor determining the high risk of cardiovascular diseases. The subject of modern research was the study of the clinical role of the patient's biological age and its difference from passport age. The aim of the study was to analyze the severity of the difference in these values in real clinical practice in patients suffering from arterial hypertension (AH) on the basis of an open multicenter register to monitor the effectiveness of therapy in patients with hypertension "HYPERION", conducted by the Eurasian Association of Therapists with the support of the company "Gedeon Richter" (Hungary). Materials and methods. The study was carried out within the open multi-center register "HYPERION". The final analysis of the register included 1441 patients, including 638 men (44%), 803 women (56%) aged 24 to 90 years. All patients were observed in primary health care (55 centers in 47 cities of Russia) for hypertension, received at least two hypotensive drugs. According to the data on 1424 patients using the qrisk-2 scale of 2017 modification, the biological age was calculated. Results and discussion. The absolute majority of patients (83,7%) had biological age >70 years, while the passport age of the absolute majority (65,3%) is in the range ≥50, but ≤69 years. Median difference between biological and passport age was 15 years. On average, in men suffering from hypertension, the biological age exceeded the passport age by 17.6 years, and in women - by 13.4 years. The difference between the value of biological and passport age and the level of systolic pressure in all age groups had a direct correlation. At systolic blood pressure >181 mm Hg. the difference between biological and passport age was the maximum, reaching the highest values in the youngest age group (30-39 years). Conclusion. Analysis of the actual (biological) age should be a mandatory procedure that allows a more complete assessment of the initial therapeutic status of the patient, which is especially important in patients aged 30-50 years. This is necessary not only from the standpoint of changing the current procedure, but also to understand the patient's prognosis.